(untitled) (American Journal of Management, 2025)
This study examines the cultural underpinnings of bureaucracy by comparing the values and beliefs of bank managers with those of small business owner-managers across two culturally diverse countries: the United States and Ukraine. Survey data were collected from 168 bank managers and 163 small business owner-managers using structured questionnaires, which assessed seven cultural constructs based on Hofstede’s value-based cultural dimensions and Leung et al.’s belief-based social axioms. The findings reveal consistent cross-national differences, with bank managers exhibiting higher Power Distance, lower Social Flexibility, and lower Spirituality. These patterns may reflect characteristic features of professional banking culture and bureaucracy more broadly.